Business model innovation in China's central business district property management: The mediating role of smart service ecosystem integration and the moderating effect of institutional adaptability - Liu, Jun; Guo, Hui; Shen, Huayu (Edelweiss Applied Science and Technology, 2026)
Against the backdrop of China's Central Business Districts (CBDs) emerging as core carriers of high-quality urban economic development, this study investigates the performance transformation mechanism of business model innovation (BMI-CBD) in CBD property management enterprises, aiming to address homogeneous competition and enhance performance. Grounded in the Resource-Based View and Institutional Theory, a mediating model of "BMI-CBD→Smart Service Ecosystem Integration (SSEI)→Business Performance (BP-CBD)" is constructed, with Institutional Adaptability (IA) introduced as a dual moderating variable. Based on questionnaire data from 462 enterprises across 15 cities, analyzed via SPSS and AMOS, the findings reveal that BMI-CBD positively impacts corporate performance, with "technological application innovation" and "cooperative network innovation" as key contributors. SSEI partially mediates the relationship, and IA positively moderates direct and mediating effects—more prominently in first-tier cities. This study integrates SSEI and IA into the research framework, providing theoretical support for overcoming the "innovation-performance" bottleneck and practical guidance for differentiated innovation strategies.